2016
DOI: 10.5424/fs/2016252-07432
|View full text |Cite
|
Sign up to set email alerts
|

Forest structure, diversity and regeneration potential along altitudinal gradient in Dhanaulti of Garhwal Himalaya

Abstract: Aim of the study: The aim of the present study was to understatnd the forest composition, structure, diversity and regeneration potential along altitudinal gradient.Area of study: The study was carried out in Dhanaulti forest which falls under temperate region of Garhwal Himalaya in Uttarakhand state, India.Material and methods: Vegetation analysis was carried out using 10 quadrats at each altitude using a quadrat size of 10×10 m 2 . In each quadrat, categories of trees >30 cm cbh were considered as trees, 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The dominance value (Ds) recorded in present study (0.93) corresponds well with that recorded from other temperate forests, which ranged from 0.135-0.97 (Saha et al 2016;Ndah et al 2013). The Pielou evenness index (e) recorded from the present study (0.92) revealed that there is an even distribution of species within the forest.…”
Section: Floristic Diversity and Compositionsupporting
confidence: 87%
“…The dominance value (Ds) recorded in present study (0.93) corresponds well with that recorded from other temperate forests, which ranged from 0.135-0.97 (Saha et al 2016;Ndah et al 2013). The Pielou evenness index (e) recorded from the present study (0.92) revealed that there is an even distribution of species within the forest.…”
Section: Floristic Diversity and Compositionsupporting
confidence: 87%
“…However, numerous studies in this area mainly focused on the elevational patterns of species richness (Acharya, Vetaas, & Birks, ; Grytnes & Vetaas, ; Hu et al, ; Joshi & Bhatt, ; Pan et al, ). Studies on beta diversity in the Himalayas have focused on plants in northwest Himalayan region (de Bello, Dolezal, Ricotta, & Klimesova, ; Saha, Rajwar, & Kumar, ) and trans‐Himalayan region (Paudel & Vetaas, ). To identify comprehensive beta diversity patterns, more rigorous studies in different regions for different taxa are needed.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, at the altitude of 1250-1275 m above sea level, a sample plot of 0.5 ha may be considered adequate ( Figure 2). Referring to research results, elsewhere, it is possible that the cumulative number of species will increase sharply when the range altitude is widened (Aiba and Kitayama 1999;Grell et al 2005;Devlal and Sharma 2008;Baniya et al 2012;Saha et al 2016).…”
Section: Species Compositionmentioning
confidence: 95%